Innovation Driven Enterprise, Sustainable Business and Firm Financial Performance - Rijanto, Arief (The Asian Journal of Technology Management (AJTM), 2018)
Abstract Innovation should be followed by profitable commercialization to have a sustainable business. Teece (1986) identified that it is often not the innovator who introduces a new process, product or service who profits the most from an innovation, but instead suppliers, cooperators, customers and competitors. In emerging markets, especially in Indonesia, it is challenging to do innovation due to the lack of infrastructure. This study explores innovation-driven enterprise relationships with firm financial performance measures by firm profitability. To identify the innovation-driven enterprise financing capabilities and innovation, the study used company age, R&D expense, sales, sales growth, debt ratio and retained earnings as independent variables. Firm profitability performance was measured by return on assets (ROA). R&D expenses of innovation-driven enterprises had a positive correlation with firm financial performance. Sales and retained earnings had a positive correlation with R&D expense. However, company age, debt ratio and sales growth had a weak negative correlation with corporate innovation activities. Retained earnings had a positive correlation and was the biggest determinant of firm profitability. It was shown that innovation-driven enterprises in Indonesia are financing their innovation with retained earnings (internal financing) and not debt (external financing).Keywords: Innovation, sustainable business, financial performance, R&D expense, internal financing